Emergence of microbial resistance against nanoparticles: Mechanisms and strategies - Kamat, Siya; Kumari, Madhuree (Frontiers in Microbiology, 2023)
Antimicrobial nanoparticles have gained the status of new generation of drugs which can kill the bacterial pathogens by multiple means, however, nanoparticles resistance acquired by some bacterial pathogens has evoked a cause of concern. Reports have suggested that bacteria can develop nanoparticles, specifically metal nanoparticles resistance, by mechanisms: nanoparticle transformation-induced oxidative stress, membrane alterations, reversible adaptive resistance, irreversible modifications to cell division and change in the bacterial motility and resistance. The surface properties, concentration and aggregation of nanoparticles, and biofilm forming and metal exclusion capacity, R plasmid and flagellin synthesis by bacteria are crucial factors to decide the development of nanoparticles resistance in bacteria. Studies have reported the resistance reversal by modifying the surface corona of nanoparticles or inhibiting flagellin production by bacterial pathogens. Further, a strict regulation regarding use and disposal of nano-waste across the globe, firm knowledge of microbe-nanoparticles interaction and regulated disposal of nanoparticles in soil and water is required to stop microbes developing nanoparticle resistance.